Epidemiology of drug-resistant tuberculosis in Bahrain, five years review - AlKhawaja, Safaa (Archives of Community Medicine and Public Health, 2020)
Introduction: Tuberculosis (TB) remains a major cause of morbidity and mortality worldwide, drug resistance is one of the major contributors to that. No existing published data about the burden of Multi-Drug Resistant (MDR) TB in the kingdom of Bahrain, the aim of our study is to estimate the prevalence of MDR TB in the kingdom and to define its resistance profile. Materials and methods: Retrospective observational study of patients with clinical diagnosis of TB between January 2014 and December 2018, cases with positive MTB culture were included for further analysis based on the results of phenotypic drug susceptibility testing to first line antituberculous. Result of molecular testing (MTB PCR & rifampicin resistant gene) were also retrieved and included in the analysis. Results: During the study period, the incidence of TB in Bahrain have dropped from 17 per 100,000 population in 2014 to 11 per 100,000 population in 2018. A total of 946 patients were reported to the public health with clinical diagnosis of TB, out of which; Five hundred and eighty eight (59%) had confirmed positive culture of Mycobacterium Tuberculosis (MTB). MDR TB was identified among 15 out of the 588 positive isolates (3%). Majority of MDR (12cases ,80%) were Non Bahraini and 10 cases, (67%) were males, pulmonary involvement encountered among 11 cases (73%). Discussion: Our rate of MDR is comparable to other reported data among neighboring Arabian Gulf countries who illustrated an average of 4% MDR-TB prevalence. Similar prevalence rate was estimated among European countries (3.8%). Among other drug resistance pattern, isoniazid monoresistnt was the most predominant resistant pattern among our population, it account for 9% among all tested isolates, this in agreement with most other previous studies among different population. Conclusion: Incidence of MTB in Bahrain is dropping, our MDR TB rate is comparable to other reported data from developed countries.